Quantum decoherence effects in neutrino oscillations at DUNE (2019)
In this work, we analyze quantum decoherence in neutrino oscillations considering the open quantum system framework and oscillations through matter for three-neutrino families. Taking the Deep Underground Neutrino Experiment as a case study, we performed sensitivity analyses for two neutrino flux configurations, finding sensitivity limits for the decoherence parameters. We also offer a physical interpretation for a new peak which arises at the ?e appearance probability with decoherence. The sensitivity limits found for the decoherence parameters are ?21?1.2×10-23 GeV and ?32?7.7×10-25 GeV at 90% C.L. © 2019 authors.